Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s10072-022-06142-4
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent CNS tumors and multiple sclerosis: retrospective single-center cohort study and lessons for the clinical management

Abstract: Introduction The concurrent presence of both central nervous system (CNS) tumors and multiple sclerosis (MS) poses various diagnostic and therapeutic pitfalls and makes the clinical management of such patients challenging. Methods In this retrospective, single-center cohort study, we searched our clinical databases (2006–2019) for patients with concurrent CNS tumors and MS and described their disease courses. Age at diagnosis of the respective disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In a more recent retrospective study involving 16 PwMS treated for a CNS tumor, no association was found between the risk of MS inflammatory activity (clinical/radiological) and prior exposure to radiotherapy or radiosurgery. 177 Among these patients, 62% had undergone radiotherapy or radiosurgery. Although the occurrence of MS inflammatory activity appeared to be more frequent in patients who had received radiotherapy or radiosurgery than those who had not, this difference was not statistically significant (66.7% vs. 33.3%, p = 0.238).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a more recent retrospective study involving 16 PwMS treated for a CNS tumor, no association was found between the risk of MS inflammatory activity (clinical/radiological) and prior exposure to radiotherapy or radiosurgery. 177 Among these patients, 62% had undergone radiotherapy or radiosurgery. Although the occurrence of MS inflammatory activity appeared to be more frequent in patients who had received radiotherapy or radiosurgery than those who had not, this difference was not statistically significant (66.7% vs. 33.3%, p = 0.238).…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent retrospective study involving 16 PwMS treated for a CNS tumor, no association was found between the risk of MS inflammatory activity (clinical/radiological) and prior exposure to radiotherapy or radiosurgery. 177 Among these patients, 62% had undergone radiotherapy or radiosurgery.…”
Section: Additional Inquiries Related To Question 5: Do Cancer Treatm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reviewing the literature, we found only two recent retrospective studies. 4,5 The first, focused on the clinical course of MS in patients with breast cancer and their experiences dealing with both conditions. 4 Authors highlighted concerns raised by neurologists and oncologists regarding the concurrent use of immunosuppressive and anticancer therapies.…”
mentioning
confidence: 99%
“…The other study, 5 described the clinical course of 16 patients with central nervous system (CNS) tumours and MS. They reported that 25% patients discontinued the MS treatment after oncological diagnosis and 31% never initiated it.…”
mentioning
confidence: 99%